2007
DOI: 10.1007/s00198-007-0370-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of osteoporosis in patients requiring spine surgery: incidence and significance of osteoporosis in spine disease

Abstract: The patients over 50 year-old who need spine operation have osteoporosis often. In conclusion, the number of spine operations in elderly patients is increasing and the incidence of osteoporosis in spine surgery patients is also increasing. We strongly recommend an evaluation for osteoporosis and post-operative treatment for osteoporosis in patients over 50 years old, especially for female patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
142
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(147 citation statements)
references
References 17 publications
1
142
1
3
Order By: Relevance
“…However, due to reduced bone quality in an osteoporotic patient, this treatment technique is a major challenge for both the orthopedic surgeon and engineers. A high number of patients undergoing spine surgery over the age of 50 suffer from osteopenia and osteoporosis (46% and 31%, respectively) [45] . The common problems associated with pedicle screws are screw bending, breakage, and loosening.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to reduced bone quality in an osteoporotic patient, this treatment technique is a major challenge for both the orthopedic surgeon and engineers. A high number of patients undergoing spine surgery over the age of 50 suffer from osteopenia and osteoporosis (46% and 31%, respectively) [45] . The common problems associated with pedicle screws are screw bending, breakage, and loosening.…”
Section: Discussionmentioning
confidence: 99%
“…5 Despite the prevalence, a survey of spine surgeons recently found that only 22% performed DXA and only 11% checked metabolic laboratory values prior to performing noninstrumented fusion. 7 Multiple studies have explored the ability of diagnostic CT scanning to identify osteopenia and osteoporosis both based on HU values obtained from the spine 30,34 and proximal humerus.…”
Section: Hu Value and Osteoporosismentioning
confidence: 99%
“…Decreased bone density secondary to osteoporosis and osteomalacia represents a serious risk factor for both bony fracture and spinal instrumentation failure (5,8,11,21,24). One of the most common and potentially treatable causes of pseudarthrosis or instrumentation failure in patients undergoing spinal fusion is poor bone mineral density (BMD) resulting from age-related vertebral osteoporosis (7).…”
Section: Introductionmentioning
confidence: 99%